Trematode larval infections in snails collected from aquaculture ponds in Ha Noi and Yen Bai, Vietnam - Manh Hung, Nguyen (Academia Journal of Biology, 2022)
The hot-spots of transmission of food-borne zoonotic trematodes in northern Vietnam have been known as the integrated fish-livestock (VAC- Garden, Fish pond, Poultry shed) ponds. A cross-sectional study was conducted in Ha Noi capital and Yen Bai province to investigate the trematode larval infections (cercariae) in freshwater snails in these areas. Snails were collected from 35 VAC ponds, including 25 grow-out and 10 nursery ponds. A total of 13,895 specimens of 12 snail species were examined for cercariae shedding. Six of 12 snail species including Melanoides tuberculata, Tarebia granifera, Radix auriculata, Gyraulus convexiusculus, Bithynia fuchsiana and Parafosarulus manchouricus, shed cercariae. Seven cercarial types were detected. The amount of snails and the prevalent infection in nursery ponds were 1.14 and 1.3 times higher than in grow-out ponds, respectively. Thus, VAC ponds in northern Vietnam are still the hot-spot for trematode larval infection.